Belle the birthday fairy - Meadows, Daisy (Rainbow magic, 2012)
When a perpetually disgruntled Jack Frost steals Belle the Birthday Fairy's three magic presents to ensure that no one will have a happy birthday, Rachel and Kirsty lend their assistance to recover the stolen magical objects.